The Level of Hazardous Waste Management Compliance Based on Government Regulation 101/2014 across Firms in Bandar Lampung - Bambang Prasetio; Merza Rahmawati (Penerbit Kemala Indonesia, 2019)
Management of hazardous waste that does not meet the requirements can cause impacts on human health and also environmental pollution such as accidents when transporting in accordance with procedures, storage areas it is not accordance with requirements, the presence of leakage, Hazardous abuse, personnel neglect, symbol giving incompatible and others. To avoid these negative impacts, it is required for every person or activity / business that produces waste to manage Hazardous waste in accordance with government regulation 101 of 2014 concerning Hazardous Waste Management. This research was conducted in April - November 2018. In industrial companies that already have Hazardous Waste TPS licenses, government and private in Bandar Lampung City, became the research location and particularly in the field of Occupational Health and Safety (OHSAS) which manages Hazardous waste in the industry. The industries that were the objects of this study consisted of 2 industries managed by government and the private sector in Bandar Lampung City namely mining company and medical eye center. Data observation and information to evaluate compatibility waste management that has been regulated in regulation No. 101/2014. The results showed, analysis and evaluation can later be used as a basis for consideration or input to the company and the Dinas Lingkungan Hidup Bandar Lampung.